Emerging Role of MicroRNAs in the Therapeutic Response in Cervical Cancer: A Systematic Review - Ravegnini, Gloria; Gorini, Francesca; Dondi, Giulia; Tesei, Marco; De Crescenzo, Eugenia; Morganti, Alessio G.; Hrelia, Patrizia; De Iaco, Pierandrea; Angelini, Sabrina; Perrone, Anna Myriam (Frontiers in Oncology, 2022)
Cervical cancer is a common female cancer, with nearly 600,000 cases and more than 300,000 deaths worldwide, every year. From a clinical point of view, surgery plays a key role in early cancer management, whereas advanced stages are treated with chemotherapy and/or radiation as adjuvant therapies. Nevertheless, predicting the degree of cancer response to chemotherapy or radiation therapy at the diagnosis in order to personalize the clinical approach represents the biggest challenge in locally advanced cancers. The feasibility of such predictive models has been repeatedly assessed using histopathological factors, imaging and nuclear methods, tissue and fluid scans, however with poor results. In this context, the identification of novel potential biomarkers remains an unmet clinical need and miRNAs represent an interesting opportunity. With this in mind, the aim of this systematic review was to map the current literature on tumor and circulating miRNAs identified as significantly associated with therapeutic response in cervical cancer; finally a perspective point of view sheds light on the challenges ahead in this tumor.